Post-thaw non-cultured and post-thaw cultured equine cord blood mesenchymal stromal cells equally suppress lymphocyte proliferation in vitro. - Lynn B Williams; Laurence Tessier; Judith B Koenig; Thomas G Koch (PLoS ONE, 2014)
Multipotent mesenchymal stromal cells (MSC) are receiving increased attention for their non-progenitor immunomodulatory potential. Cryopreservation is commonly used for long-term storage of MSC. Post-thaw MSC proliferation is associated with a lag-phase in vitro. How this lag-phase affect MSC immunomodulatory properties is unknown. We hypothesized that in vitro there is no difference in lymphocyte suppression potential between quick-thawed cryopreserved equine cord blood (CB) MSC immediately included in mixed lymphocyte reaction (MLR) and same MSC allowed post-thaw culture time prior to inclusion in MLR. Cryopreserved CB-MSC from five unrelated foals were compared using two-way MLR. For each of the five unrelated MSC cultures, paired MLR assays of MSC allowed five days of post-thaw culture and MSC included in MLR assay immediately post-thawing were evaluated. We report no difference in the suppression of lymphocyte proliferation by CB-MSC that had undergone post-thaw culture and MSC not cultured post-thaw (p<0.0001). Also, there was no inter-donor variability between the lymphocyte suppressive properties of MSC harvested from the five different donors (p = 0.13). These findings suggest that cryopreserved CB-MSC may have clinical utility immediately upon thawing. One implication hereof is the possibility of using cryopreserved CB-MSC at third party locations without the need for cell culture equipment or competencies.